Prevalence, risk factors, and management of dementia and mild cognitive impairment in adults aged 60 years or older in China: a cross-sectional study. (December 2020) - Jia, Longfei; Du, Yifeng; Chu, Lan; Zhang, Zhanjun; Li, Fangyu; Lyu, Diyang; Li, Yan; Li, Yan; Zhu, Min; Jiao, Haishan; Song, Yang; Shi, Yuqing; et al.
Summary: Background: China has a large population of older people, but has not yet undertaken a comprehensive study on the prevalence, risk factors, and management of both dementia and mild cognitive impairment (MCI). Methods: For this national cross-sectional study, 46 011 adults aged 60 years or older were recruited between March 10, 2015, and Dec 26, 2018, using a multistage, stratified, cluster-sampling method, which considered geographical region, degree of urbanisation, economic development status, and sex and age distribution. 96 sites were randomly selected in 12 provinces and municipalities representative of all socioeconomic and geographical regions in China. Participants were interviewed to obtain data on sociodemographic characteristics, lifestyle, medical history, current medications, and family history, and then completed a neuropsychological testing battery administered by a psychological evaluator. The prevalence of dementia (Alzheimer's disease, vascular dementia, and other dementias) and MCI were calculated and the risk factors for different groups were examined using multivariable-adjusted analyses. Findings: Overall age-adjusted and sex-adjusted prevalence was estimated to be 6·0% (95% CI 5·8–6·3) for dementia, 3·9% (3·8–4·1) for Alzheimer's disease, 1·6% (1·5–1·7) for vascular dementia, and 0·5% (0·5–0·6) for other dementias. We estimated that 15·07 million (95% CI 14·53–15·62) people aged 60 years or older in China have dementia: 9·83 million (9·39–10·29) with Alzheimer's disease, 3·92 million (3·64–4·22) with vascular dementia, and 1·32 million (1·16–1·50) with other dementias. Overall MCI prevalence was estimated to be 15·5% (15·2–15·9), representing 38·77 million (37·95–39·62) people in China. Dementia and MCI shared similar risk factors including old age (dementia: odds ratios ranging from 2·69 [95% CI 2·43–2·98] to 6·60 [5·24–8·32]; MCI: from 1·89 [1·77–2·00] to 4·70 [3·77–5·87]); female sex (dementia: 1·43 [1·31–1·56]; MCI: 1·51 [1·43–1·59]); parental history of dementia (dementia: 7·20 [5·68–9·12]; MCI: 1·91 [1·48–2·46]); rural residence (dementia: 1·16 [1·06–1·27]; MCI: 1·45 [1·38–1·54]); fewer years of education (dementia: from 1·17 [1·06–1·29] to 1·55 [1·38–1·73]; MCI: from 1·48 [1·39–1·58] to 3·48 [3·25–3·73]); being widowed, divorced, or living alone (dementia: from 2·59 [2·30–2·90] to 2·66 [2·29–3·10]; MCI: from 1·58 [1·44–1·73] to 1·74 [1·56–1·95]); smoking (dementia: 1·85 [1·67–2·04]; MCI: 1·27 [1·19–1·36]), hypertension (dementia: 1·86 [1·70–2·03]; MCI: 1·62 [1·54–1·71] for MCI), hyperlipidaemia (dementia: 1·87 [1·71–2·05]; MCI: 1·29 [1·21–1·37]), diabetes (dementia: 2·14 [1·96–2·34]; MCI: 1·44 [1·35–1·53]), heart disease (dementia: 1·98 [1·73–2·26]; MCI: 1·17 [1·06–1·30]), and cerebrovascular disease (dementia: 5·44 [4·95–5·97]; MCI: 1·49 [1·36–1·62]). Nine of these risk factors are modifiable. Interpretation: Dementia and MCI are highly prevalent in China and share similar risk factors. A prevention strategy should be developed to target the identified risk factors in the MCI population to thwart or slow down disease progression. It is also crucial to optimise the management of dementia and MCI as an important part of China's public health system. Funding: Key Project of the National Natural Science Foundation of China, National Key Scientific Instrument and Equipment Development Project, Mission Program of Beijing Municipal Administration of Hospitals, Beijing Scholars Program, Beijing Brain Initiative from Beijing Municipal Science & Technology Commission, Project for Outstanding Doctor with Combined Ability of Western and Chinese Medicine, and Beijing Municipal Commission of Health and Family Planning.